Low back pain educational programs and quality of life in women living with chronic low back pain: a semi experimental study - sedighe sadat tavafian; Ahmadreza Jamshidi; shohreh shahmohammadi (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Chronic low back pain is a major medical problem in the world which affect the quality of human life seriously. This study aimed to explore the impact of educational programs on quality of life in women with low back up to 6 months after intervention. Methods: This is a semi experimental study that was carried out in Rheumatology Research Center of Tehran University of Medical Sciences. There were 27 eligible patients who suffering from chronic low back pain entered in the study. All participants divided into groups of 6 to 8 members and were provided with a four-hour training session of physiotherapy and psychology followed by telephone counseling. Sf-36 questionnaire was completed at initial of the study and 6 months after intervention. Data were analyzed by independent Sample t-test and paired t-test. Findings: Totally 27 participants with mean age of 51.62 ± 9.29 entered into the study. Pain duration and treatment duration of the participants were 148.59±26.37 and 63.44±58.81, respectively. Between sciatic pain and physical function (p=0.02), physical functioning (p=0.01), bodily pain (p=0.01), and psychological functioning (p=0.03) were statistically significant differences. Quality of life scores increased after interventional in all aspects and show significant differences in the areas of physical pain (p=0.004), general health (p= 0.002) and mental health (p=0.002).